Construction of The Trip Jump Test in Athletic Student - Raffly Henjilito; Alficandra Alficandra; Zulkifli Zulkifli; Muqimul Haqqi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this research is to make improvements in the triple jump test. The component that is repaired is only in the process of executing the jump starting from the prefix, jump, step, jump and landing. Usually the triple jump test is only by making the farthest jump and then measuring how far the jump is made. To find out the quality of the jumps of Riau Islamic University athletic students, of course there must be test instruments and test norms for these athletes. This research method uses research and development methods or research and development. The validation of research and development instruments used content validation which was carried out by several experts (expert judgment) who made one test and measurement expert and two experts in the field of athletics. Based on the results of the expert test evaluation analysis, the triple jump instrument is declared valid and reliable, so that it can be used as research material for athletic students.